A STUDY ON BUILDING CONSTRUCTION INVESTMENT FEASIBILITY - Meriana Wahyu Nugroho; Lyya Supriono (Universitas Islam Malang, 2020)
The level of society’s awareness on education is very high. The society’s enthusiasm to take a higher education is enormous. Every year the society’s interest in joining Hasyim Asy'ari University of Tebuireng Jombang is increasing. For this reason, Hasyim Asy'ari University of Tebuireng Jombang plans to add the classes by constructing new buildings that can accommodate more students each year. Every construction certainly has a risk. To anticipate this, a feasibility study is carried out at the early stages of construction planning so that later the construction runs well. There are three methods used to analyze investment feasibility, namely, Net Present Value (NPV) method, Benefit Cost Ratio (BCR) method and Internal Rate of Return (IRR) method. Besides using those methods, the payback period for the building construction project of Hasyim Asy'ari University of Tebuireng Jombang is also calculated. Based on the results of the analysis conducted, it was found that the construction of Hasyim Asy'ari University of Tebuireng Jombang was feasible to be carried out referring to the NPV and B/C values which were higher than one and the IRR value was higher than MARR and the payback period was for 7 years and 5 months. Thus, the investment project is declared feasible to proceed.